# math

posted by .

USING FORMULAR METHOD SOLVE D EQUATION(M-3)²=121

• math -

M-3=±11
M₁₂=14
M₂ =-8

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### Math

Using the intersection method, I need to solve the following equation: 5x-3.3=x-2.1 Can you point me on the right path?
3. ### math

solve for x without using a calculator 5^(x+1) = 25 i know that x would equal 1 because 5^2 is 25, but i don't know how to show how to solve it All you need to do is what you just did: Explain that if x = 1, the equation is satisfied. …
4. ### Math

Using formular express the equation. 5x2-6x-3=0
5. ### Math

Solve the system using any algebraic method. 2x - 2y + z = 3 5y - z = -31 x + 3y + 2z = -21 ______________________ The answer I got for this is ( -26, 6,67) but I know its wrong and I don't know why. Help please >< my work is …
6. ### 8th grade math HELP URGENT!!!

Solve Each equation by first dividing each side of the equation by the number outside the parentheses. When would you recommend using this method to solve an equation?
7. ### Math

I still don't know how to directly solve this problem. Can someone guide to solve this system of equation by using the substitution method?
8. ### Math

Hi! Can someone help me with this? Thanks! Directions: Solve this equation by doing it twice; one time using the substitution method and one time using the graphing method. x + 2y = 1 5x – 4y = -23
9. ### Math

Hi! Can someone help me with this? Thanks! Directions: Solve this equation by doing it twice; one time using the substitution method and one time using the graphing method. x – 2y = 0 3x – y^2 = 0
10. ### Math

Hi! I need help with this. Thank you! Directions: Solve this equation by doing it twice; one time using the substitution method and one time using the graphing method. -2/3 x + y = 2 2x – 3y = 6

More Similar Questions